Taboo Language on Physical and Mental Limitations in the Pidie Raya Community - Mohd. Harun; Junaidi Junaidi; Dian Fajrina (Universitas Syiah Kuala, 2019)
The purpose of this study is to describe types of taboo language with regard to physical and mental limitations in the Pidie Raya community, which includes Pidie Regency and Pidie Jaya Regency. This field research with a qualitative approach used a descriptive-analytical method. The data of this research were taboo languages in a spoken form related to physical and mental limitations in the Pidie Raya community. The data were obtained from 16 informants who settled in eight villages within the sub-districts of Muara Tiga, Padang Tiji, Trienggadeng and Meureudu, in the regency of Pidie and Pidie Jaya. The data were collected using structured interview techniques supported by inducement techniques. The data were analyzed qualitatively through several stages (a) selecting data, (b) describing the whole data, (c) grouping data based on their types, and (d) analyzing data followed by drawing conclusions. The results showed that the taboo languages related to physical limitation include a) inherited physical deficiencies/abnormalities, and (b) physical limitations due to illness. While taboo languages related to mental limitation includes (a) mental disorders, (b) weak-minded, and (c) psychological disorders. Some taboo words about one's physical and mental limitations in the Pidie Raya community can be expressed in the form of refinement or euphemism. This is intended to prevent social inequalities among the members of the community.